Psychometric Properties of the Fear of Progression Questionnaire for Children (FoP-Q-SF/C) - Luz, Johanne Katrin; Martini, Julia; Clever, Katharina; Herschbach, Peter; Christiansen, Holger; Schepper, Florian (Klinische Pädiatrie, 2020)
Background Recent research shows that parents of children suffer from fear of progression (FoP), the fear of further disease progression. It is most possible that children also develop FoP, which could impair treatment and psychological health. The aim of this study is to adapt the adult’s version of the Fear of Progression Questionnaire – Short Form (FoP-Q-SF) for children and to examine the psychometric properties in pediatric cancer patients.Patients 32 pediatric cancer patients between 10 and 18 years with different diagnoses and in different treatment states participated in this study.Method In the cross-sectional study participants completed the adapted Fear of Progression Questionnaire – Short Form for Children (FoP-Q-SF/C) and self-report measures assessing quality of life, depression, fear and coping satisfaction.Results The questionnaire (FoP-Q-SF/C) showed adequate psychometric properties (Cronbachs α=0.86) and good results for construct validity. Significant medium to large correlations of children’s FoP was observed with quality of life (r=− 0.37), depression (r=0.52), fear (r=0.33 – 0.76), and satisfaction with coping (r=− 0.44). One-fifth of the sample was classified as having high FoP with values over 37.Conclusions The FoP-Q-SF/C is a short, economic questionnaire that is applicable in children with cancer. Clinicians can use the questionnaire to explore specific fear and the need for psychosocial support. Further research for specific treatment approaches for FoP in pediatric cancer patients are warranted.Hintergrund Aktuelle Forschungsergebnisse zeigen, dass Eltern krebskranker Kinder unter Progredienzangst (PA), der Angst vor dem Fortschreiten einer Erkrankung leiden. Es scheint naheliegend, dass auch Kinder diese Ängste entwickeln, was die Behandlung und die psychologische Gesundheit beeinflussen kann. Ziel der Studie ist die Adaption des Progredienzangst-Fragebogens (FoP-Q-SF) für Kinder und die Ermittlung der psychometrischen Eigenschaften für pädiatrische Onkologiepatienten.Patienten 32 pädiatrische Krebspatienten zwischen 10 und 18 Jahren mit unterschiedlichen Krebsdiagnosen und in unterschiedlichen Behandlungsstadien nahmen an der Studie teil.Methode In der Querschnittsstudie beantworteten die Teilnehmenden den adaptierten Progredienzangst-Fragebogen-Kurzversion für Kinder (FoP-Q-SF/C) und Selbstbeantwortungsfragebögen zu Lebensqualität, Depression, Angst und Copingzufriedenheit.Ergebnisse Der Fragebogen (FoP-Q-SF/C) zeigte adäquate psychometrische Eigenschaften (Cronbachs α=0,86) und Konstrukvalidität. Signifikante Korrelationen wurden zwischen Progredienzangst und Lebensqualität (r=− 0,37), Depression (r=0,52), Angst (r=0,33–0,76), und Copingzufriedenheit (r=− 0,44) gefunden. Ein Fünftel der Stichprobe zeigte hohe Progredienzangstwerte mit Werten über 37.Schlussfolgerung Der FoP-Q-SF/C ist ein kurzer, ökonomischer Fragebogen, der für krebskranke Kinder passend ist. Kliniker können den Fragebogen einsetzen, um PA und die Notwendigkeit von psychosozialer Unterstützung zu erfassen. Weitere Forschungsarbeiten für spezifische Behandlungsansätze von PA in der pädiatrischen Onkologie sind wünschenswert.
Keywords: cancer; child; fear of progression; psychometric; psychosocial support; questionnaire